2013
DOI: 10.1186/1471-2482-13-s2-s14
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and cancer: epidemiological evidence and mechanism of selected aspects

Abstract: BackgroundPopulations living in the area of the Mediterranean Sea suffered by decreased incidence of cancer compared with those living in the regions of northern Europe and US countries, attributed to healthier dietary habits. Nowadays, we are assisting to a moving away from the traditional Mediterranean dietary pattern, but whether this changing is influencing risk of cancers is still unclear. The aim of the study was to review recent evidence on potential relationship between the adherence to the Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 104 publications
(102 reference statements)
3
82
0
3
Order By: Relevance
“…Indeed, a J-shaped curve with a protective effect of 15-35 g of red wine intake was observed in men, regardless of the overall dietary habits of the participants. The inverse association between moderate red wine intake and prevalence of CRC may be, at least partially, attributed to its content of antioxidant compounds, such as polyphenols, that have been demonstrated to have antimutagenic and antiproliferative properties (7). Despite these new findings on red wine consumption and CRC, we did not find any protective effect of red wine, although the detrimental effect of alcohol intake was attenuated among participants who were more adherent to the MD.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, a J-shaped curve with a protective effect of 15-35 g of red wine intake was observed in men, regardless of the overall dietary habits of the participants. The inverse association between moderate red wine intake and prevalence of CRC may be, at least partially, attributed to its content of antioxidant compounds, such as polyphenols, that have been demonstrated to have antimutagenic and antiproliferative properties (7). Despite these new findings on red wine consumption and CRC, we did not find any protective effect of red wine, although the detrimental effect of alcohol intake was attenuated among participants who were more adherent to the MD.…”
Section: Discussionmentioning
confidence: 73%
“…The combination of such foods included in the pattern provides a high amount of antioxidants such as flavonoids, carotenoids, and vitamins that have been shown to protect against cancer (7). Moreover, the high content of fiber, folate, and a favorable fatty acid profile may increase the link of this dietary pattern with protective mechanisms preventing carcinogenesis (8,9).…”
Section: Introductionmentioning
confidence: 98%
“…The Mediterranean-type diet (MeDi) is a healthy dietary pattern (Scarmeas et al 2006b) that has been associated with lower risk of a wide variety of diseases including cardiovascular diseases (Estruch et al 2013;Gardener et al 2011), dementia (Scarmeas et al 2006b), Parkinson's disease (Alcalay et al 2012), cancer (Grosso et al 2013), and others. The MeDi is characterized by high intake of vegetables, legumes, fruits, cereals, fish, monounsaturated fatty acids, low intake of saturated fatty acids, dairy products, meat and poultry, and mild to moderate ethanol use (Scarmeas et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using various different indices to assess the association of OPLC with adherence to the Mediterranean diet, Filomeno et al and Li et al found strong evidence for a beneficial role of this diet on OPLC risk [19,27]. A recent review by Grosso et al discussed many plausible biological mechanisms that explain the protective role patterns such as the Prudent/healthy and the Mediterranean have on the risk of cancer [50]. Fruits and vegetables are rich in antioxidants such as carotenoids, vitamin C, vitamin E, selenium, dietary fiber (and its components), dithiolthiones, glucosinolates (isothiocyanates and indoles), polyphenols, protease inhibitors, allium compounds, plant sterols, and limonene [51].…”
Section: Discussionmentioning
confidence: 99%